KINERJA PELAYANAN PUBLIK DI KABUPATEN CILACAP (Pengaruh Motivasi Kerja, Komitmen Pegawai dan Disiplin Kerja Terhadap Kinerja Pegawai Negeri Sipil di Kabupaten Cilacap) - Akhmad Edi Susanto; Wahyuningrat Wahyuningrat; Denok Kurniasih (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2017)
The purpose of this study was to examine the effect of work motivation, employee commitment, and work discipline on the performance of civil servants of Cilacap Regency either partially or simultaneously. The research method used is survey. Samples were taken by proportionate stratified random sampling method. While the data obtained from the questionnaire were analyzed with multiple linear regression statistics. The results showed that the performance of Cilacap Regency civil servants in moderate category. The result of the analysis of the variables is known that jointly work motivation, employee commitment, and work discipline affect the performance of 42%, while the remaining 58% is influenced by other variables outside the research model. The results of this study provide input to the government of Cilacap Regency to pay attention to work discipline and work motivation to improve the performance of civil servants. This can be done through improving regulatory understanding, encouraging employees to be consistent, creating honest competition, rewarding employee performance, and creating a harmonious and familial working environment. Keywords: Discipline, Performance, Commitment, Motivation, Public Service, Cilacap